Strength of reinforced fibrous foamed concrete-filled hollow section - Abd Rahman, Norashidah; Khairuddin, Siti Amirah Azra; Jamaluddin, Norwati; Mohd Jaini, Zainorizuan (Trans Tech Publications, 2018)
At present, research on concrete-filled sections extends to using lightweight concrete to reduce the total weight of such structures. However, research on concrete-filled hollow sections (CFHS) using foamed concrete remains ongoing. Therefore, this study was conducted to determine the strength of reinforced fibrous foamed CFHSs. Two types of fibre, namely, steel and polypropylene fibres, were used. A short-column specimen was prepared and tested under compression load. Result shows that adding steel fibre to foamed concrete indicates a higher strength than adding polypropylene fibre. The strength of the CFHS is increased by adding reinforced bar and fibre in foamed concrete.